The Role of Reviewer Characteristics on the Diversity of Successful Applicants - Gavrilova-Zoutman, Evelina; Juranek, Steffen (Organization Science, 2025)
In their efforts to foster diversity and talent, organizations, banks, and venture capitalists utilize the expertise of reviewers to evaluate applications from a broad range of applicants. Reviewers make decisions under different types of cognitive load, such as the necessity to aggregate complex information and workload pressure. To cope with the stress, reviewers might use automatic biases to make decisions faster, which can result in lower organizational diversity. We explore the characteristics of reviewers in a particular setting—patent applications at the U.S. Patent and Trademark Office (USPTO). We leverage quasi-exogenous variation from the random assignment of patent examiners, allowing us to find the causal impact of applicant gender and examiner characteristics on the application success rate. We find evidence that applicants with more female-sounding names have a 3.6-percentage-point lower likelihood of patent approval. We find that a high workload of the examiner leads to a decrease in the likelihood that the patent application of a female inventor would be approved, consistent with theories on coping strategies when experiencing cognitive load. Our results extend to applications filed by teams of inventors. These results suggest that it is essential to manage the stress related to reviewers’ workloads to guarantee a variety of successful candidates. Supplemental Material: The online appendix is available at https://doi.org/10.1287/orsc.2023.17910 .